Indelible Coloniality and Emergent Decoloniality in Colombian-Authored EFL Textbooks: A Critical Content Analysis - Astrid Núñez Pardo (Ikala: Revista de Lenguaje y Cultura, 2022)
The use of Colombian-authored EFL textbooks as subalternation instruments, the instrumentalization of grammar and foreign methodologies, and the imperialism of a profit-driven publishing industry perpetuates colonial links. This article reports a critical content analysis of six Colombian-authored EFL textbooks from local and foreign publishers. It was framed within a sociocritical paradigm, which included interviews with four authors, six teachers, and two editors. Findings reveal three triads of decolonial criteria: (a) The triad of ontological criteria unsettles the reproduction of foreign beliefs, behaviours, values, and ideologies; (b) the triad of epistemological criteria subverts North and West dominant knowledge and culture, and (c) the triad of power criteria withstands globalised and neoliberal discourses imposed through teaching methods, curricula, materials, testing, training, and standardised English varieties. The findings also indicate that there are still colonial traces in the representation of gender, races, sexual orientations, capacities, and social classes. Thus, developing efl materials from a decolonial perspective contests the commercial, standardised, and colonised textbooks to build contextualised and decolonised efl materials otherwise that are sensitive to cultural diversity. This academic endeavour exhorts teachers to assume a critical stance towards EFL materials content, learning activities and strategies, underpinning language pedagogies, iconography, language policy, and assessment practices, and to exert their agency to contest hegemony and recreate situated EFL pedagogical practices.